Understanding transatlantic relations : whither the West? - Simoni, Serena (Routledge advances in international relations and global politics, 2013)
In light of the Arab Spring and after days of public quarreling that highlighted the divisions among NATO's members on an agreement to give command of the ""no-fly"" zone in Libya to the Alliance, it is evident that the U.S. is having problems engaging with its European allies and partners. Why is this happening? Breaking away from the conventional way to study transatlantic relations, Serena Simoni uses a Constructivist theoretical lens to argue that the transatlantic partners' changing identities since the early 1990s have influenced their political interests and, as a consequence,